A model to simulate the haemodynamic effects of right heart pulsatile flow after modified Fontan procedure. Issue 2 (February 1992) - Tamaki, S; Kawazoe, K; Yagihara, T; Abe, T
Abstract : The effect of pulsatile pulmonary flow after the modified Fontan procedure was examined in a model that simulated the right heart. An inlet overflow tank (preload), axial pulsatile pump, Wind-Kessel model (afterload), and an outlet overflow tank were connected in series. The standard conditions were flow 2.00 l/min with 12 mm Hg preload pressure, 3.0 Wood units resistance, and an outlet overflow tank pressure at 6 mm Hg. The pump rate was set at 80 beats/min. The simulated pulmonary arterial pressure and pulmonary flow waves produced by this model closely resembled those obtained from patients who had undergone the modified Fontan procedure. All variables except the preload were fixed and changes in pulmonary flow were examined at preload pressures of 8, 12, 15, and 17 mm Hg. As the peak pulmonary arterial pressure increased so did pulmonary flow, until it was greater than during the non-pulsatile state. Because the afterload of this model was fixed, this result suggests that there was a concomitant decrease in resistance. This model indicates that pulsatile pulmonary blood flow is likely to have a beneficial effect on the pulmonary circulation after the modified Fontan procedure.